Spotlight on ORNAC Members - Harley, Catherine (Operating Room Nurses Association of Canada Journal, 2012)
Kimberly Long is a Perioperative Registered Nurse who recently completed the RNFA Program and is a resource nurse for the Urology service at the North Bay Regional Health Center (NBRHC) in North Bay, ON. Kim works as an RNFA/RN in a composite position that is approximately a half and half split and carries an expectation of both call and evening shifts.